The study of employees’ job satisfaction in Sarawak Economic Development Corporation (SEDC) / Sharifah Fadzlina Wan Bujang - Wan Bujang, Sharifah Fadzlina (2012)
Job satisfaction has been defined as a pleasurable emotional state resulting from the appraisal of one’s job which is an affective reaction to one’s job or/and an attitude towards one’s job. The purpose of the present study is to examine the relationship between Personality, Working Environment and Pay Level with Job Satisfaction and the paper type is Research Paper. This study was conducted by distributing questionnaires to random staff of Sarawak Economic Development Corporation (SEDC) and by using the Likert Scale to determine employees’ scale on Job Satisfaction. 60 out of 100 sets of questionnaire were collected from employees. Results from the survey showed the relationship between Personality, Work Environment and Pay Level with Job Satisfaction at SEDC Sarawak. Recommendations have been provided in order to improve and gain better results.